Prevalence of Psychological Distress in Suriname In Urban and Rural Areas: The Suriname Health Study - PW Gunther; M Sanches; CCF Smits; ISK Krishnadath (Journal of Human Psychology, 2017)
Objective: To describe the presence of mental distress in a representative sample of the Surinamese ethnic groups in the population, across urban and rural areas. Design and Methods: The Kessler Psychological Distress Scale was applied to data from the Suriname Health Study (n=5,434 (15 to 65 years)) designed according to WHO Steps guidelines,to determine prevalences for mental distress in all living areas. Calculations were made in subgroups of sex, age, ethnicity, education, income, marital and employment status. The Odds Ratio (OR) for Sex and Ethnicity was estimated for mild-moderate and severe mental distress. Results: An overall prevalence of 3.8% (95%CI, 3.3-4.4) was observed for severe mental distress, 4.9% (95%CI, 4.4-5.5) for moderate mental distress and 10.8% (95%CI,10.0-11.6) for mild mental distress. The OR for mild-moderate and severe mental distress was 0.7 and 0.5 for men compared to women and higher prevalence of all categories of mental distress were found in women compared to men. Respondents with lower education and lower income showed higher prevalence of all categories of mental distress. Prevalence was also higher among respondents living in urban versus rural coastal areas, among singles versus people living with a partner and in unemployed versus employed. Maroons had higher Odds for mild-moderate and severe mental distress compared to Hindustani. Amerindian and Javanese had lower Odds for mild-moderate mental distress and Creole had lower Odds for Severe mental distress compared to Hindustani. Conclusions: Overall 19.5% of respondents reported mental distress. The main risk factors were female gender, Maroon ethnicity, low level of education and income, living in urban areas, unemployment and being single.
Keywords: Ethnicity